2021
DOI: 10.1186/s12912-021-00544-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-trial perceptions of a symptom-based TB screening intervention in South Africa: implementation insights and future directions for TB preventive healthcare services

Abstract: Background Tuberculosis is a top-10 cause of under-5 mortality, despite policies promoting tuberculosis preventive therapy (TPT). We previously conducted a cluster randomized trial to evaluate the effectiveness of symptom-based versus tuberculin skin-based screening on child TPT uptake. Symptom-based screening did not improve TPT uptake and nearly two-thirds of child contacts were not identified or not linked to care. Here we qualitatively explored healthcare provider perceptions of factors tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Prior to trial implementation, a standardized child contact management form will be implemented in both settings to standardize data collection by all facilities in both arms. The tool was adapted from a previous trial by each country team and in conjunction with the parent IMPAACT4TB project [ 6 , 20 , 21 ]. Children will be evaluated monthly until they complete TPT, as per the Ethiopian and South African National Guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to trial implementation, a standardized child contact management form will be implemented in both settings to standardize data collection by all facilities in both arms. The tool was adapted from a previous trial by each country team and in conjunction with the parent IMPAACT4TB project [ 6 , 20 , 21 ]. Children will be evaluated monthly until they complete TPT, as per the Ethiopian and South African National Guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…A recent review estimated that less than a third of eligible child contacts initiated TPT, and less than a third of those who initiated, completed six months of isoniazid [38]. Qualitative research identified challenges at various levels but specifically noted a lack of training for healthcare workers and inadequate systems to monitor TPT delivery [38,39]. TPT completion is not monitored and reported, but plans are currently in place to include these in the National Indicator Data Set in 2022.…”
Section: South Africa: Key Programmatic Opportunities and Challenges ...mentioning
confidence: 99%